THE REFLECTION OF LOYALTY IN ERNEST HEMINGWAY’S THE OLD MAN AND THE SEA - Delli Sabudu (Jurnal Penelitian Humaniora, 2020)
This study aims at revealing the reflection of loyalty in Hemingway’s The Old man and the Sea. The focus of this study only on the character of Manolin, he is a learner of the old fisherman. This study is categorized as qualitative research design which is the data collected in the form of words rather than numbers. It is also used objective approach that the analysis focused only at the novel itself and the interrelationship between its internal parts of the elements. The results reveal that the character of Manolin was reflected loyalty to the old fisherman through his commitment over many challenges, his high attention to the old fisherman, and his devotion to him. It was mentioned as follows: firstly by showing his commitment over many challenges, secondly by showing high attention to Old man (Santiago), and the third showing his devotion to the old man (Santiago). The result presented here may facilitate information that Loyalty is the positive mental attitude that can be learned through the character of Manolin. It is also given to the student in English Education Department to duplicate the loyalty from Manolin because this is a positive attitude and can be used as a moral lesson.